2012
DOI: 10.1074/jbc.m112.404277
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Acidic Nucleoplasmic DNA-binding Protein (And-1) in the Regulation of Prereplicative Complex (pre-RC) Assembly in Human Cells

Abstract: Background:The assembly of a replicative helicase MCM2-7 onto replication origins is essential for initiation of DNA replication. Results: And-1 facilitates assembly of MCM2-7 onto replication origins. Conclusion: And-1 is proposed to be a critical regulator of prereplicative complex assembly in human cells. Significance: These studies reveal a novel role for human And-1 in the licensing of replication origins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…While the established cellular function is pre-RC activation for DNA synthesis, WDHD1 has also been implicated in a role in pre-RC assembly, functioning as a DNA replication initiation factor (19). The known DNA replication initiation factors, Cdt1 and Cdc6, have been shown to be required for rereplication (9,10,14,34,44,63).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the established cellular function is pre-RC activation for DNA synthesis, WDHD1 has also been implicated in a role in pre-RC assembly, functioning as a DNA replication initiation factor (19). The known DNA replication initiation factors, Cdt1 and Cdc6, have been shown to be required for rereplication (9,10,14,34,44,63).…”
Section: Discussionmentioning
confidence: 99%
“…HMG boxes are found in many eukaryotic proteins involved in chromatin assembly, transcription, and replication. In addition to its established role in pre-RC activation (19)(20)(21), WDHD1 is also involved in pre-RC assembly (19). The WDHD1 gene is localized adjacent to replication foci, interacts with human primase-DNA polymerase/MCM10, and is required for DNA synthesis (20,22,23).…”
mentioning
confidence: 99%
“…Silver staining was carried out with the SilverQuest TM silver staining kit (Invitrogen). Mass spectrometry was performed as described earlier (Li et al, 2012b).…”
Section: Plasmids and Antibodiesmentioning
confidence: 99%
“…Previous studies by others and us showed that the acidic nucleoplasmic DNA-binding protein 1 (And-1) is a replisome component and is required for efficient DNA replication in unperturbed cells (Zhu et al, 2007;Errico et al, 2009;Gambus et al, 2009;Im et al, 2009;Yoshizawa-Sugata & Masai, 2009;Bermudez et al, 2010;Li et al, 2012b). Ctf4/Mcl1, the ortholog of And-1 in yeast, is required for chromosome transmission fidelity, sister chromatin cohesion, DNA damage repair, maintenance of genome integrity, and the regulation of telomere replication (Kouprina et al, 1992;Hanna et al, 2001;Williams & McIntosh, 2002;Mayer et al, 2004;Tsutsui et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation